F156. The estimated F latency and its participation in the diagnosis of S1 radiculopathy. (May 2018) - Arciniega Martínez, Genny G.; Tello, Armando; Pilar Rodríguez Rodríguez, Maria del; Serrano, Fabiola
Abstract : Introduction: The assessment of lumbosacral radiculopathies include F-waves studies. However, its diagnostic contribution is in debate. The aim of this study was to determine the diagnostic contribution of the tibial nerve F-wave estimated Vs: F-wave minimum latency in patients with lumbo-sacral radiculopathy. These parameters are the most widely used in clinical practice. We compared the resultant of these differences with electromyography (EMG) confirmed S1 radiculopathies and MRI findings. Methods: We studied 39 patients, 18 years and older, with lumbosacral radiculopathy symptoms, lasting more than a month. All had MRI studies. We preformed nerve conduction studies, including late responses and EMG. Exclusion criteria: peripheral neuropathy, genetic or neurodegenerative diseases of muscle and peripheral nerves. We recorded 10 F-waves by stimulating tibial nerves at the ankle. We evaluate minimal latency (Fmin) and F-estimated. We made 2 groups, one with MRI evidence of S1 radiculopathy and the other group without MRI evidence of S1 compression. We used statistical software (SPSS 20.0) to calculate the odds ratios (OR) to quantify the magnitude of the association; p  < 0.05 was significant. Results: We evaluated 39 patients (M:24/F:15), made two groups: G1 patients with radiological evidence of S1 radiculopathy; G2 patients without radiological evidence of S1 radiculopathy, patients with radiculopathy of L3, L4, L5, not S1 radiculopathy and the healthy side of patients with unilateral S1 radiculopathy. Ten patients had radiological evidence of left S1 radiculopathy; only 1 had F-wave minimum latency greater than F-wave estimated. Eleven patients had MRI evidence of right S1 radiculopathy, but only three had F-wave minimum latency greater than the F-wave estimated. When comparing patients with MRI evidence of S1 radiculopathy with F-wave minimum latency greater than F-wave estimated on the left side, the p value was 0.751 (not significant); on the right side, the p value was 0.091 (not significant). Left OR was 1.5 (IC 0.1–18) and right OR was 4.8 (IC 0.6–34). Conclusion: To our knowledge, there are no studies comparing the estimated F-wave/minimum F-wave, with MRI in patients with S1 radiculopathy. Mauricio, et al. ( Muscle Nerve 49: 809–813, 2014) compared the estimated F-wave latency with the minimum F-wave latency in S1 radiculopathy, with electromyography as the "gold standard". They showed a low sensitivity of the F-wave results for the assessment of S1 root injury as in the present study. In agreement with Mauricio et al., we conclude that the estimate F-wave is not a useful tool as part of the electrodiagnostic evaluation for lumbosacral radiculopathies. One drawback of this study is that imaging studies might contribute to high false-positive rates of S1 radiculopathies.